2019
DOI: 10.1089/neu.2018.6114
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Biochemical Correlates of Mitochondrial Dysfunction after Low-Intensity Primary Blast Exposure

Abstract: Our observations demonstrate that primary LIB injury comprises an 'invisible' injury in the presence of nanoscale myelinated axonal injury and mitochondrial damages associated with neurobehavioral impairments. Further, we found LIB induced oxidative stress associated with mitochondrial dysfunction mainly at 7 and 30 DPI. Our study provides key insights into the pathogenesis and potential treatment of primary LIB injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…In general, animal studies of LLB articulated methods to induce blast exposure in well-controlled environments ( 45 66 ), examined longitudinal outcomes associated with LLB ( 46 , 64 ) or repeated exposures to LLB ( 49 ), or assessed the impact of environmental characteristics on outcomes associated with LLB ( 58 ). Studies frequently examined neurological outcomes, such as neuroinflammation and neurodegeneration ( 51 , 57 , 61 63 ) and damage to specific brain regions or types of cells ( 53 , 65 ). Animal studies also examined outcomes related to mental health ( 54 , 55 ) and auditory ( 47 ), visual ( 48 , 56 ), vestibular ( 52 ), and vascular ( 50 ) systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, animal studies of LLB articulated methods to induce blast exposure in well-controlled environments ( 45 66 ), examined longitudinal outcomes associated with LLB ( 46 , 64 ) or repeated exposures to LLB ( 49 ), or assessed the impact of environmental characteristics on outcomes associated with LLB ( 58 ). Studies frequently examined neurological outcomes, such as neuroinflammation and neurodegeneration ( 51 , 57 , 61 63 ) and damage to specific brain regions or types of cells ( 53 , 65 ). Animal studies also examined outcomes related to mental health ( 54 , 55 ) and auditory ( 47 ), visual ( 48 , 56 ), vestibular ( 52 ), and vascular ( 50 ) systems.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes in studies using rats ranged from 10 to 180, with 75% of studies including fewer than 100 subjects. Other species studied included mice ( 46 , 52 , 63 , 64 ), pigs ( 58 ), and chinchillas ( 47 ). Sample size for these species varied from 14 (chinchillas) to 115 (pigs).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of low level exposure without a direct impact to the head, this study indicated that median levels of serum Nf-L and tau were elevated (although tau did not meet statistical thresholds). Exposure is reported to impact brain tissues in a way that may mirror a sub-concussive event [24,25], causing cytoskeletal abnormalities and demyelination in rodent models [26][27][28]. In animal models, serum tau is elevated within 6h-1d of and the heavy chain isoform of neurofilament is increased within 2h after mild exposure [29].…”
Section: A Subset Of Tbi-related Proteins Are Potential Biomarkers Ofmentioning
confidence: 99%
“…Quantitative TMT proteomic studies have also been conducted in single low-intensity blast (mTBI) injury studies at 2 and 24 hr, and 7 and 30 days postinjury (Song et al., 2019). Animals revealed mitochondrial and axonal ultrastructural changes.…”
Section: Discussionmentioning
confidence: 99%